1999
DOI: 10.1007/s005350050245
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory response of colon tissue to dextran sulfate sodium-induced colitis

Abstract: Depletion of goblet cells (the main mucin-producing cells in the colon) is one of the most reliable histological characteristics of ulcerative colitis, whereas a major symptom of this disease is bloody diarrhea containing a large amount of mucus. The discrepancy between these phenomena was investigated in a time-course study in rats with experimental colitis induced by treatment with oral dextran sulfate sodium (DSS) for 1, 3, or 5 days. Biochemical analysis showed a reduction in mucin content in the distal si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
2
12
1
Order By: Relevance
“…Contrary to the present results, other investigators found increased number of goblet cells in dextran sulfate sodium-colitis rats [48]. The authors explained their findings by the heterogeneity of colonic inflammation with depleted goblet cell areas and increased in another areas with mucus overproduction previously suggested by Nakano et al [49].…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to the present results, other investigators found increased number of goblet cells in dextran sulfate sodium-colitis rats [48]. The authors explained their findings by the heterogeneity of colonic inflammation with depleted goblet cell areas and increased in another areas with mucus overproduction previously suggested by Nakano et al [49].…”
Section: Discussioncontrasting
confidence: 99%
“…Similar findings have been shown in the IL10 −/− colitis model [34]. It is not clear, whether the loss of mucus is caused by actual goblet cell depletion or whether the goblet cells are still present, but have lost their characteristic morphology due to decreased mucus contents [33][34][35][36]. Our finding that TFF3 mRNA and protein -which is specifically expressed in intestinal goblet cells -is still present in areas of extensive mucus depletion indicates the latter.…”
Section: Discussionsupporting
confidence: 77%
“…Preparation of probes: Fragments of mouse TFF-3 cDNA were generated by RT-PCR from mouse embryo (17th gestational day) Poly A+ RNA and used to prepare the following subclone in pBluescript KS(+): mTFF3, basepair 36-238 (mTFF3, EMBO database AQC number NM_011575) (confirmed by sequencing (MWG Biotech, Ebersberg, Germany)). Generation of 35 S-UTP labeled antisense and sense probes by in vitro transcription as well as the in situ hybridization procedure was performed as described by Pyke et al [16].…”
Section: Trefoil Factor 3 Detectionmentioning
confidence: 99%
“…Previous studies from our group (1) and others (34,36) indicate that DSS colitis pathology develops progressively over time. Therefore, in order to better understand temporal changes in genome expression profiles, 3% DSS-mediated tissue histopathology was evaluated and confirmed at days 0, 2, 4, and 6.…”
Section: Dss Increases Colitis Parameters Progressively Over Timementioning
confidence: 93%